TLR3 and GLUL orchestrate inflammatory and homeostatic imbalance in osteoarthritis - Wang, Jing; Xu, Shenghao; Chen, Bo; Peng, Peiqiang; Wang, Kai; Qin, Yanguo (Frontiers in Immunology, 2026)
IntroductionOsteoarthritis (OA) is a degenerative joint disease marked by chronic inflammation, extracellular matrix degradation, and dysregulated cell death. The roles of apoptosis-, autophagy-, and ferroptosis-related genes in OA pathogenesis remain unclear.MethodsIntegrated bioinformatics analyses were conducted on public GEO datasets to identify apoptosis-autophagy-ferroptosis-related genes (AAFRGs). TLR3 and GLUL were identified using LASSO, random forest, and SVM-RFE algorithms. Immune infiltration analysis, immunohistochemistry, and functional assays in human chondrocytes were performed, and ACLT-induced rat OA models were used for in vivo validation.ResultsTLR3 was upregulated and associated with pro-inflammatory immune cells, while GLUL was downregulated and correlated with anti-inflammatory signatures. TLR3 knockdown reduced inflammation, apoptosis, and aberrant mineralization, partially restoring extracellular matrix integrity. GLUL overexpression promoted cellular homeostasis. In rats, TLR3 inhibition and PRP treatment decreased pro-inflammatory cytokines (IL-1β, TNF-α), reduced matrix-degrading enzymes (MMP3, MMP13), and restored GLUL and IL-10 levels.Discussion/ConclusionTLR3 and GLUL orchestrate inflammatory responses and homeostatic imbalance in OA, representing potential biomarkers and therapeutic targets for diagnosis and intervention.